Application of design for assembly (DFA) in small and medium industries (SMI) - Md. Sirat, Rozlina (Faculty of Mechanical Engineering, 2003)
Design For Assembly (DFA) is a well-known technique, but little published work exists for its detailed implementation. This research has developed a DFA framework suitable for implementation in Small and Medium Sized Industries (SMI). A survey of design practices in Malaysia revealed that there were about five different types of practices involved in product development in Malaysia. Some problems in implementing DFA were also reported by users or potential users in the survey. For the purpose of research, a case study on an SMI company making automotive parts was used. A proposed framework was developed in which the product development cycle was outlined in detail and various stages were identified in which DFA could be implemented.